A WSSL Implementation for Critical CyberPhysical Systems Applications - Rocha, Márcia Cunha (2023)
The advancements in wireless communication technologies have enabled unprecedented pervasiveness and ubiquity of Cyber-Physical Systems (CPS). Such technologies can now empower true Systems-of-Systems (SoS), which cooperate to achieve more complex and efficient functionalities, such as vehicle automation, industry, residential automation, and others. However, for CPS applications to become a reality and fulfill their potential, safety and security must be guaranteed, particularly in critical systems, since they rely heavily on open communication systems, prone to intentional and non-intentional interferences. To address these issues, in this work, we propose designing a Wireless Security and Safety Layer (WSSL) architecture to be implemented in critical CPS applications. WSSL increases the reliability of these critical communications by enabling the detection of communication errors. Otherwise, it increases the CPS security using a message signature process that uniquely identifies the sender. So, this work intends to present the WSSL architecture and its implementation over two different scenarios: over Message Queue Telemetry Transport (MQTT) protocol and inside a simulation environment for communication between Unmanned Aerial Vehicles (UAVs) and Ground Control Stations in case of Beyond Visual Line of Sight (BVLOS) applications. We aim to prove that the WSSL does not significantly increase the system payload and demonstrate its safety and security resources, allowing it to be used in any general or critical CPS.